The hidden end of the value chain: potentials of integrating gender, households, and consumption into agrifood chain analysis - Brückner, Meike; Sardadvar, Karin (Frontiers in Sustainable Food Systems, 2023)
The aim of this perspective paper is to reinforce the analysis of gender relations in agrifood chain research and integrate the household and the work and consumption taking place there. In the value chain discourse, approaches that integrate households and consumption as an analytical dimension exist, but the last stage often remains hidden. To take a holistic view on value chains integrating the hidden end, we apply feminist economic perspectives and gender analysis to agrifood chains. This paper builds on our own research while integrating it with other scholars’ empirical work and the theoretical literature concerning gender and value chains. Drawing on empirical examples from both the Global North and South (e.g., on the meat, tomato, seafood, and African Indigenous Vegetables chains), we illustrate the importance of households and consumption to value chain analysis with three examples: Firstly, we demonstrate how commercialization in agrifood chains impacts consumption practices and the food-related care work of women; secondly, we discuss how market-oriented reforms to production in a globalized economy restrict control and access to food for producers; and thirdly, we illustrate that consumer appetite influences working conditions in food production and policies. The examples underscore the fact that households and consumption are not isolated components, but are embedded in a complex agrifood system. In the final part of the paper, we propose an agenda for making this hidden end of the value chain and its links to gender, the household, and consumption more visible.